2022
DOI: 10.3390/ma15155107
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Parameters of Leather in Relation to Technological Processing of the Footwear Uppers

Abstract: This paper aimed to define two critical mechanical properties of leather—Young’s modulus and Poisson ratio—essential to the virtual simulation of the behaviour of the footwear uppers against the manufacturing operations of stitching and perforating. The following technological aspects were considered to analyse the materials from manufacturing conditions point of view: the number of layers (one layer and two layers), the nature of the materials used for uppers subgroups (calfskin-outer upper, sheep leather-lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…A comparison with the mechanical properties presented by similar materials as animal leather is quite difficult, considering the wide variability of thickness and properties presented by animal skins from different sources. However, in general terms, it can be observed that most of the tested materials present comparable strength, stiffness and ultimate elongation as animal skin, for cow/calf leather, reported values are in the range of 3–13 MPa for strength, 50–100 MPa for tensile modulus and 10–30 % for break elongation [ 45 , 46 ]. The data are reported as average ± 1 standard deviation, repetitions for each specimen is 5.…”
Section: Resultsmentioning
confidence: 99%
“…A comparison with the mechanical properties presented by similar materials as animal leather is quite difficult, considering the wide variability of thickness and properties presented by animal skins from different sources. However, in general terms, it can be observed that most of the tested materials present comparable strength, stiffness and ultimate elongation as animal skin, for cow/calf leather, reported values are in the range of 3–13 MPa for strength, 50–100 MPa for tensile modulus and 10–30 % for break elongation [ 45 , 46 ]. The data are reported as average ± 1 standard deviation, repetitions for each specimen is 5.…”
Section: Resultsmentioning
confidence: 99%
“…Depending on the target of the experiments, different S/N ratios can be selected. Under these different selections, S/N ratios quantify how the variation in the response happened relative to the target value [7]. Three different S/N characteristic formulations (conditions) are present in the following equations [13].…”
Section: Designing the Experimentmentioning
confidence: 99%
“…Different thread sizes may affect the tensile strength and overall integrity of the seam. Additionally, stitching direction, whether parallel or perpendicular to the leather grain, can influence the seam's resistance to stress and deformation [7]. The stitching direction, whether parallel or perpendicular to the grain of the leather, can influence seam strength.…”
Section: Introductionmentioning
confidence: 99%
“…The tensile curves (Figure 3) of materials used for footwear upper exhibit a nuanced response with characteristics encompassing non-elastic, elastic, and plastic-type behaviours [38]. Consequently, the tensile curve can be divided into distinct regions.…”
Section: Properties Of Materialsmentioning
confidence: 99%